2021
DOI: 10.1155/2021/6680935
|View full text |Cite
|
Sign up to set email alerts
|

Natural Phytochemicals as Novel Therapeutic Strategies to Prevent and Treat Parkinson’s Disease: Current Knowledge and Future Perspectives

Abstract: Parkinson’s disease (PD) is the second-most common neurodegenerative chronic disease affecting both cognitive performance and motor functions in aged people. Yet despite the prevalence of this disease, the current therapeutic options for the management of PD can only alleviate motor symptoms. Research has explored novel substances for naturally derived antioxidant phytochemicals with potential therapeutic benefits for PD patients through their neuroprotective mechanism, targeting oxidative stress, neuroinflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 354 publications
0
30
0
Order By: Relevance
“…Protocatechuic aldehyde is another phenolic acid gained from the root of Salvia miltiorrhiza, which has a protective effect on mitochondria by blocking ROS production and keeping the activity of complex I in MPP + -incubated SH-SY5Y cells evaluated in an in vitro experiment [15]. In this line, another phenolic acid, caffeic acid, obtained from tea, wine, coffee, etc., blocked the production of ROS and normalized the activity of mitochondria in the 6-OHDA-induced SH-SY5Y cellular model of PD [54]. In the MPTP animal model of PD, caffeic acid's phenethyl ester reduced dopaminergic neurodegeneration and dopamine loss.…”
Section: Polyphenols Effects On Mitochondria In Pdmentioning
confidence: 95%
See 3 more Smart Citations
“…Protocatechuic aldehyde is another phenolic acid gained from the root of Salvia miltiorrhiza, which has a protective effect on mitochondria by blocking ROS production and keeping the activity of complex I in MPP + -incubated SH-SY5Y cells evaluated in an in vitro experiment [15]. In this line, another phenolic acid, caffeic acid, obtained from tea, wine, coffee, etc., blocked the production of ROS and normalized the activity of mitochondria in the 6-OHDA-induced SH-SY5Y cellular model of PD [54]. In the MPTP animal model of PD, caffeic acid's phenethyl ester reduced dopaminergic neurodegeneration and dopamine loss.…”
Section: Polyphenols Effects On Mitochondria In Pdmentioning
confidence: 95%
“…Curcumin, a polyphenol gained from Curcuma longa, protected mitochondrial function in PD by blocking the activity of MPP + and ROS production in an in vivo and in vitro experiment [36,42,59] and preventing mitochondrial membrane damage in PD [18,19,34]. Targeting the exact mechanism, vanillin, a phenolic aldehyde, reduced rotenone-induced ROS production and mitochondrial malfunction in SH-SY5Y cells [54]. As another phenolic compound, luteolin, obtained from the ripe seed of Perilla frutescens, also played a preventive role in ROS production and maintained mitochondria's activity at a normal level [46,60].…”
Section: Polyphenols Effects On Mitochondria In Pdmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decades many reviews and papers have demonstrated the role of oxidative stress in the pathogenesis of these neurodegenerative diseases, and the administration of both natural and synthetic antioxidant molecules was studied in diverse clinical trials ( Blesa et al, 2015 ; Kim et al, 2015 ; Ganguly et al, 2021 ). The beneficial effects of the Mediterranean diet against age-related cognitive decline have been highlighted ( Gardener and Caunca, 2018 ; Balakrishnan et al, 2021 ), and they were associated to the high consumption of olive oil ( Kalatsbari, 2013 ). It was recently revealed that the poly(phenolic) components of extra virgin olive oil could be neuroprotective and ameliorative against these diseases, by working on several clinical biomarkers and molecular targets ( Spagnuolo et al, 2016 ; Dinda et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%